Glucose Fluctuations Aggravate Myocardial Fibrosis via the Nuclear Factor-κB-Mediated Nucleotide-Binding Oligomerization Domain-Like Receptor Protein 3 Inflammasome Activation - Zhang, Zhen-Ye; Dang, Shi-Peng; Li, Shan-Shan; Liu, Ying; Qi, Miao-Miao; Wang, Ning; Miao, Ling-Feng; Wu, Ying; Li, Xiao-Yan; Wang, Chun-Xin; Qian, Ling-Ling; Wang, Ru-Xing (Frontiers in Cardiovascular Medicine, 2022)
Background: Glucose fluctuations may be associated with myocardial fibrosis. This study aimed to investigate the underlying mechanisms of glucose fluctuation-related myocardial fibrosis. Methods: Streptozotocin (STZ)-injected type 1 diabetic rats were randomized to five groups: the controlled blood glucose (CBG) group, the uncontrolled blood glucose (UBG) group, the fluctuated blood glucose (FBG) group, the FBG rats injected with 0.9% sodium chloride (NaCl) (FBG + NaCl) group and the FBG rats injected with MCC950 (FBG + MCC950) group. Eight weeks later, left ventricular function was evaluated by echocardiography and myocardial fibrosis was observed by Masson trichrome staining. The primary neonatal rat cardiac fibroblasts were cultured with different concentrations of glucose in vitro. Results: The left ventricular function was impaired and myocardial fibrosis was aggravated most significantly in the FBG group compared with the CBG and UBG groups. The levels of interleukin (IL)-1β, IL-18, transforming growth factor-β1 (TGF-β1), collagen type 1 (collagen I), nuclear factor (NF)-κB and nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome were significantly increased in the FBG group. In vitro, the inhibition of NF-κB and inflammasome reversed these effects. In vivo, NLRP3 inhibition with MCC950 reversed left ventricular systolic dysfunction and myocardial fibrosis induced by glucose fluctuations. Conclusions: Glucose fluctuations promote diabetic myocardial fibrosis by the NF-κB-mediated inflammasome activation.